Estimating Friction Coefficient and Fraction of Sliding in Friction Stir Welding - Zhihan Zhang (Journal of Engineering Science and Technology Review, 2014)
The heat generation, contact state, material flow and friction coefficient are all intertwined during friction stir welding (FSW) because of the fully thermomechanical coupling nature of FSW. The value of friction coefficient and the fraction of sliding will dominate heat generation which is the driving force to make the FSW process successful. This work detailedly clarified how to roughly estimate the fraction of sliding and friction coefficient at the tool/workpiece interface. Results showed that friction coefficients in FSW of various materials were in a range of 0.2-0.56. The fraction of sliding was significantly affected by friction coefficient. The fraction of sliding was in a range of about 73-88% for FSW of Al1100-H14 alloy and about 38-65% for FSW of Al7050-T7451 alloy. Moreover, the fraction of sliding increased with decreasing heat input.